Attitudes, beliefs and knowledge about medical cannabis among nurses and midwives in Cyprus: a cross-sectional descriptive correlational study - Sokratous, Sokratis; Kaikoushi, Katerina; Mpouzika, Meropi; Alexandrou, George; Karanikola, Maria (My University, 2022)
Background: There is a lack of evidence on healthcare professionals’ attitudes, knowledge, and beliefs about medical cannabis in Cyprus and across the world. Therefore, the present study aimed to explore the attitudes, beliefs, and knowledge about MC use among nurses and midwives in Cyprus. Special focus was given to differences across gender, age, religion, marital status, and years of work experience. Methods: A descriptive, cross-sectional correlational study with internal comparisons was conducted during the 26th Nurses and Midwives Congress in Cyprus. All active nurses and midwives (convenience sampling), from the private and national healthcare services (n = 526) were eligible to participate. To analyze the data, the Pearson Chi-square test for group differences was employed, and descriptive and inferential statistics were assessed. Results: The final sample population consisted of 232 nurses and midwives (response rate of 46.4%). In total, 67(28.9%) participants were male, and 165(71.1%) were female. Cypriot nurses and midwives reported lack of knowledge regarding the risks and benefits about MC use to patients. However, specific number of participants believed MC use was considered acceptable for the patients with persistent muscle spasms, insomnia/sleeping disorders, mental health conditions, and terminal illnesses. The vast majority of the participants believed that formal training on MC should be integrated into academic programs, and expressed the necessity of urgent training under the current curriculum, as well as, educational training programs about MC use should be integrated into the practice/clinical practice. Concerning the socio-demographic characteristics of the participants, gender had a statistically significant positive effect on participants’ attitudes and beliefs about MC (p < 0.01, 26.8% vs. 13.4%). Male and unmarried participants reported higher frequency about cannabis use for recreational purposes, compared with female group (p < 0.01, 22.8%Vs 11.4%). Unmarried participants agreed that using cannabis might develop serious mental health risks compared with married participants group (p < 0.05, 77.9% vs. 66.8%). Conclusions: The conclusions seem to be rather recommending in favor of MC use. Participants proposed enriching nursing curricula with theoretical and clinical/laboratory courses about MC during studies and clinical practice. Additional tailoring interventions should be established to decrease recreational cannabis use among Cypriot nurses and midwives.
Keywords: Cypriot nurses; Midwives; Attitudes; Beliefs; Knowledge; Medical cannabis